2004
DOI: 10.1111/j.0001-6349.2004.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine ultrasonography in monitoring the outcome of medical abortion in a clinical setting

Abstract: Routine TVS 2-3 weeks after medical abortion appears to be an efficient means of accurately identifying the cases of ongoing pregnancy and diagnosing a complete abortion. Although TVS could be used as an adjunct to clinical examination to diagnose an incomplete expulsion, it does not accurately differentiate those women who require surgical intervention from those who do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The same conclusion has also been drawn by other workers [11]. We found that the amount of bleeding and incidence of incomplete abortion increased with the rise in the number of days of amenorrhoea in our series which is similar to other studies [3].…”
Section: Discussionsupporting
confidence: 93%
“…The same conclusion has also been drawn by other workers [11]. We found that the amount of bleeding and incidence of incomplete abortion increased with the rise in the number of days of amenorrhoea in our series which is similar to other studies [3].…”
Section: Discussionsupporting
confidence: 93%
“…These conclusions are also supported by others. 22 There are limited data regarding the sonographic appearance of the uterine cavity after a medical abortion; however, more information is available regarding the sonographic appearance of the uterine cavity after a spontaneous abortion or surgical abortion in the first trimester. Bar-Hava et al 23 observed that in 77% of their cases of uterine evacuation in first-trimester TOP, a considerable amount of intrauterine content with various echogenicities was sonographically detected within 1 week of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the conclusions made by others. 22,23 The purpose of the follow-up sonographic examination in this study at day 14 was to assess retention of products. Based on these data, it is probably unnecessary to perform this follow-up examination at day 14 in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, antibiotic treatment should be initiated. [4][5][6] Ultrasound is typically the first-line investigation in suspected cases of retained products of conception (RPOC). Variable amount of echogenic or heterogeneous material within the endometrial cavity, presence of vascularity within the echogenic material supports the diagnosis, and helps to differentiate it from intrauterine blood clot.…”
Section: Introductionmentioning
confidence: 99%